The forensic implications of camouflaging: victimisation and offending in Autism and Pathological Demand Avoidance - Trundle, Grace (2021)
Social camouflaging refers to behaviours or strategies which conceal an individuals’ Autism from others. Camouflaging has also been described by individuals with Pathological Demand Avoidance (PDA). Camouflaging is reportedly used in response to threat, potentially reducing the risk of victimisation. Camouflaging can also prevent timely diagnosis and access to support, which may increase the risk of victimisation and offending behaviour. This thesis aims to examine the forensic implications of social camouflaging in association with autism and PDA traits.